The Influence Of Service Features, Perceived Convenience, And Financial Literacy On Generation Z's Decision To Use Ovo E-Wallet In Bengkulu City Brand Trust As An Intervening Variable - Chandra, Setiawan Adi; Puspita, Veny; Waliamin, Janusi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study aims to determine the Influence of Service Features, Perceived Convenience and Financial Literacy on the Decision to Use Ovo E-Wallet on Generation Z in Bengkulu City Brand Trust as an Intervening Variable, especially among generation Z in Bengkulu City. The sampling technique is Purposive side. The data collection technique in this study is a questionnaire. The sample of this study amounted to 120. The theoretical approach of this study is quantitative. The results of the study show that the independent variables of Service Features, Perceived Convenience and Financial Literacy simultaneously have a positive and significant effect on the dependent variable of the Decision to Use Ovo E-Wallet, the Service Features variable partially has a positive and significant effect on the Decision to Use Ovo E-Wallet variable, the Perceived Convenience variable partially has a positive and significant effect on the Decision to Use Ovo E-Wallet variable, and the Financial Literacy variable partially has a positive and significant effect on the Decision to Use Ovo E-Wallet variable.